Evaluation of intravenous immunoglobulin resistance and coronary artery lesions in relation to Th1/Th2 cytokine profiles in patients with Kawasaki disease. Issue 3 (25th February 2013) - Wang, Yujia; Wang, Wei; Gong, Fangqi; Fu, Songling; Zhang, Qing; Hu, Jian; Qi, Yanqi; Xie, Chunhong; Zhang, Yiying
Abstract: Objective: To investigate the roles of serum Th1 and Th2 cytokines in Kawasaki disease (KD) and determine whether the Th1/Th2 cytokine profiles in children with KD may be involved in intravenous immunoglobulin (IVIG) resistance and development of coronary artery lesions (CALs). Methods: Serum Th1 and Th2 cytokines, including interferon‐γ (IFNγ), tumor necrosis factor α (TNFα), interleukin‐10 (IL‐10), IL‐6, IL‐4, and IL‐2, were measured using a cytometric bead array in the serum of 143 patients with KD before and after treatment with IVIG (pre‐IVIG, at 3 days after temperature normalization following IVIG treatment [post‐IVIG], and 1 month posttreatment). Results: Levels of IL‐6, IL‐10, TNFα, and IFNγ were significantly increased in KD patients pre‐IVIG. Post‐IVIG, the levels of IL‐6, IL‐10, and IFNγ quickly decreased. The levels of TNFα decreased significantly after IVIG treatment in KD patients without CALs post‐IVIG and in KD patients who were IVIG responders, but increased slightly in KD patients with CALs post‐IVIG and in KD patients who were IVIG nonresponders. Before IVIG treatment, the levels of IL‐4, IL‐6, IL‐10, and IFNγ were significantly higher in KD patients with CALs than in those without CALs. The post‐IVIG levels of IL‐6 and IL‐10 were significantly higher in IVIG nonresponders than in IVIG responders. Pre‐IVIG, an IL‐10 level >8 pg/ml had a sensitivity of 75.0% and a specificity of 64.4% for predicting CALs, while a TNFα level <2 pg/ml had a sensitivity of 66.7% and a specificity of 74.2% for predicting IVIG resistance. Post‐IVIG, an IL‐6 level >10 pg/ml had a sensitivity of 67.9% and a specificity of 81.7% for predicting CALs, while an IL‐10 level >6 pg/ml had a sensitivity of 53.6% and a specificity of 86% for predicting CALs. Conclusion: Determination of the serum Th1/Th2 cytokine profile may be helpful for predicting the disease prognosis and targeting treatment strategies in patients with KD.